Manajemen Operasional Sebagai Kapabilitas Strategis Dalam Meningkatkan Daya Saing Perusahaan - Nur Fadliah Ramadani.H; Mahfud Nurnajamuddin; Nellyana Mokhtar; Ramlawati Ramlawati (Center of Economic Students Journal, 2026)
Intensifying business competition drives companies to build superior internal capabilities to sustain operations. Operations management serves as a strategic capability directly impacting competitive advantage. This study aims to analyze the role of operations management as a strategic capability in enhancing firm competitiveness through cost efficiency, quality, delivery reliability, flexibility, and continuous improvement. Employing a conceptual literature review method with thematic synthesis, secondary data was gathered from Google Scholar  and ScienceDirect (2015-2024 period) using relevant peer-reviewed article criteria. Findings show that operations management practices (process design, lean, quality management, TPM, productivity, supply chain integration) improve operational performance (cost, quality, delivery, flexibility), thereby strengthening competitive strategy. The main contribution is a conceptual framework along with implementation recommendations for managers.